Born to Code: Does the Portrayal of Computer Scientists as Geniuses Undermine Adolescent Youths' Motivational Beliefs? - Starr, Christine R. (Frontiers in Psychology, 2021)
Introduction: Computer scientists are often stereotyped as geniuses who are naturally gifted in pSTEM (physical Sciences, Technology, Engineering, and Math). Prior correlational research found that this genius stereotype is negatively related to students’ pSTEM motivation. However, the effect has not been explored experimentally to evaluate possible casual influences. Using situated expectancy-value theory as a framework, the present experiment tested whether media invoking the genius stereotype negatively impacts high school students’ expectancy and value beliefs regarding pSTEM. Methods: The sample comprised of 213 U.S. high school students (53% boys, 46% Asian). Participants read one of two versions of an article profiling a student majoring in computer science. The genius condition emphasized the student’s natural talent and the importance of being gifted for success in computer science, whereas the control condition did not mention these attributes. Pre- and post-test measures of pSTEM expectancy and value beliefs were assessed. Results & Conclusions: Students in the genius condition, but not the control condition, demonstrated a significant decline in pSTEM value beliefs. There was no effect on expectancy beliefs. Thus, popular stereotypes of persons in pSTEM as geniuses may contribute to students devaluing of pSTEM subjects. These stereotypes may be especially threatening to girls and students from minoritized backgrounds. Implications are discussed, including the need to address genius stereotypes in pSTEM classrooms.